Ein Rechenmodell zur vergleichenden Beurteilung der Verfahrenskosten bei Bodenbearbeitungsgeräten - Schäfer, Winfried (de, 1979)
High field capacity amd low energy requirements with regard to towed implements are obtained on the one hand by tractor pull capability and reducing draft requirement of the implement, on the other hand by accurate matching operating parameters of tractor and implements. This essay presents a model to calculate the minimum time and/or energy requirement combination of four wheel drive tractors and towed soil tillage implements. The results show how the variables which the farmer can influence (axle horse power, tractor weight, working width, no-slip travel speed) must be determined in order to match the factors concerned to an optimum degree.
Nimekkeen selvennys: Calculation model to compare tillage cost.
Keywords: Ra; optimointi; maanmuokkauskoneet; kustannukset; työnmenekki; tillage; calculation model; cost comparison